Enhancing sales performance of product-service systems: The role of value-based selling, price bundling, and value tools☆ - Nijssen, Edwin J.; Terho, Harri; Keränen, Joona; van der Borgh; Michel (Elsevier, 2026)
Many industrial firms struggle to sell their product-service systems (PSS) and solution offerings profitably. While prior research has underscored the role of value-based selling (VBS) in selling PSS, it has provided little insight into pricing in this context. This study examines the interplay between VBS, price bundling, and value tools when selling PSS and solutions. Building on signaling theory, we argue that VBS acts as a signal that helps customers accept a solution price bundle by focusing their attention to the total value-in-use of the bundled solution rather than its individual components. This, in turn, drives service ratio and customer growth performance. Value tools facilitate this process. To test our research hypotheses, we conduct a multi-industry survey and use a mediation-moderation model to analyze the data. Our findings show that price bundling mediates the relationship between VBS and service ratio, and that value tools boost the final step of this link. In turn, VBS and value tools directly affect customer growth performance. This study advances VBS research by explaining how VBS and organizational value assessment tools enable effective use of price bundling as a pricing mechanism to drive PSS sales performance in B2B markets.